2022
DOI: 10.1021/acs.macromol.2c01684
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Polymer-Grafted Nanoparticles in Homopolymer Blends from Simulations

Abstract: The phase behavior of polymer-grafted nanoparticles (gNPs) in homopolymer matrices is investigated using coarsegrained simulations. Simulations are performed using theoretically informed Langevin dynamics (TILD), a particle-based method that uses a particle-to-mesh scheme to efficiently calculate the nonbonded interactions. Direct two-phase simulations are used to determine coexistence curves. The phase diagram for NPs densely grafted with short A chains and blended with long B homopolymer chains is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To overcome this limitation, the strategy of anchoring polymers onto the surface of nanoparticles has emerged as a promising approach. This method produces matrix-free nanocomposites, also referred to as single-component nanocomposites, which exhibit superior homogeneity compared to those mixed directly with homopolymer matrices. Consequently, matrix-free nanocomposites have found broad applications in numerous fields, and extensive research efforts have been devoted to their preparation methods, involving chemical and physical explorations. Polymer-grafted nanoparticles (PGNPs) constitute a category of single-component nanocomposites, characterized by the grafting of various polymer types onto the surfaces of different nanoparticles, including but not limited to silica, iron oxide, and gold. This grafting process results in a hybrid material that combines the properties of the nanoparticle core with the characteristics of the grafted polymer chains. The capacity to tailor the grafted polymer chains allows for the customization of specific chemical or physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, the strategy of anchoring polymers onto the surface of nanoparticles has emerged as a promising approach. This method produces matrix-free nanocomposites, also referred to as single-component nanocomposites, which exhibit superior homogeneity compared to those mixed directly with homopolymer matrices. Consequently, matrix-free nanocomposites have found broad applications in numerous fields, and extensive research efforts have been devoted to their preparation methods, involving chemical and physical explorations. Polymer-grafted nanoparticles (PGNPs) constitute a category of single-component nanocomposites, characterized by the grafting of various polymer types onto the surfaces of different nanoparticles, including but not limited to silica, iron oxide, and gold. This grafting process results in a hybrid material that combines the properties of the nanoparticle core with the characteristics of the grafted polymer chains. The capacity to tailor the grafted polymer chains allows for the customization of specific chemical or physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…23 Using TILD, Santos and Frischknecht predicted the phase behavior of binary and ternary PNC systems, consistent with experiments and modeling. 24 In addition to bulk morphology, the surface of polymer blend films can exhibit unique properties that provide insight into PNC behavior. 25,26 For example, Jones et al first observed surface-directed spinodal decomposition (SDSD) in isotopic binary polymer blends as a result of preferential attraction of the surface for one of the components.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this athermal case, parameters like NP size, confinement, grafting density, and relative chain length of the brush and matrix lead to various structures, which in turn yield different optical and thermal properties. Notably, for densely grafted NPs in their athermal matrix, the transition from wet to dry brush occurs when the ratio of matrix to brush chain length is between 4 and 5. For sparsely grafted NPs, various structures like spherical aggregates, strings, and sheets form as a result of balancing the core–core attractions and brush dynamics. ,, When the matrix is chemically distinct from the brush, simulations and experiments show that the enthalpic interactions between the brush and matrix chains lead to phase separation in a similar fashion as the binary blends of their linear polymer counterparts. , Koski et al predicted phase diagrams of a PNC system using theoretically informed Langevin dynamics (TILD) and experimentally confirmed the prediction using silica NPs grafted with poly­(methyl methacrylate) (PMMA) in a polystyrene (PS) matrix . Using TILD, Santos and Frischknecht predicted the phase behavior of binary and ternary PNC systems, consistent with experiments and modeling …”
Section: Introductionmentioning
confidence: 99%
“…Polymer-grafted nanoparticles (PGNPs) are quite promising for the manufacturing of membrane and composite materials for gas separation, biological, , mechanical reinforcement, and optical applications . Theoretical frameworks and computer simulations are very useful in guiding and interpreting experimental studies and help resolve major design issues of industrial interest. , A variety of theoretical and simulation methodologies have been employed to address systems of PGNPs and brushes, such as the polymer reference interaction site model (PRISM), self-consistent field theory (SCFT), density functional theory (DFT), molecular dynamics (MD), dissipative particle dynamics (DPD), as well as machine-learning frameworks. , In addition to these studies, scaling laws for the height of the polymer brush have been proposed to describe the structural behavior of grafted chains in the solid/polymer interfacial region over a broad range of experimental conditions. , …”
Section: Introductionmentioning
confidence: 99%